Clinical and genetic analysis of patients with segmental overgrowth features and somatic mammalian target of rapamycin (mTOR) pathway disruption: Possible novel clinical issues. Issue 20 (8th November 2022) - Romano, Ferruccio; Madia, Francesca; De Marco, Patrizia; Ognibene, Marzia; Guerrisi, Sara; Scala, Marcello; Iacomino, Michele; Baldassari, Simona; Vercellino, Nadia; Manunza, Francesca; Tallone, Ramona; Pavanello, Marco; et al.
Abstract: Segmental overgrowth syndromes include a group of clinical entities, all characterized by the abundant proliferation of tissues or organs in association with vascular abnormalities. These syndromes show a wide spectrum of severity ranging from limited involvement of only small areas of the body to complex cases with impressive distortions of multiple tissues and organs. It is now clear that somatic mutations in genes of the phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (in brief "mTOR pathway") are responsible for such entities. Not all the cells of the body carry the same causative mutation, which is mosaic, appearing from two (or more) distinct cell lineages after fertilization. In this article, we reconsider the clinical spectrum and surveillance programs of patients with segmental overgrowth syndromes, based on the features of six patients with diverse clinical forms of overgrowth and pathogenic variants in genes of the mTOR pathway.